ANALYSIS OF TECHNICAL AND TECHNOLOGICAL FORMS OF INTERACTION BETWEEN VARIOUS TYPES OF TRANSPORT - MYTKO, MYKOLA; BURLAKA, SERHIY; YAROSHCHUK, ROMAN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The efficiency of the transport system is one of the key factors in the economic development of any country. In today's conditions of globalization and rapid growth in international trade, ensuring the reliability, speed and efficiency of transportation is becoming an important task. The growing volume of cargo and passenger flows impose new requirements on transport infrastructure, process management and the organization of intermodal interaction. Optimization of transport processes is becoming a decisive factor in increasing the efficiency of logistics systems and the competitiveness of national economies.The modern transport system involves the integration of various modes of transport, which allows for the uninterrupted delivery of goods and passengers at all stages of transportation. Technical and technological interaction between modes of transport is the basis of such an integration approach. Technical interaction includes the unification of infrastructure elements, such as cargo terminals, logistics centers and intermodal stations, as well as vehicle standards. At the same time, technological solutions are aimed at automation, digitalization of transportation management processes and the use of innovative logistics approaches.The implementation of effective interaction between modes of transport requires solving a number of problems. Among them: imperfect transport infrastructure, insufficient coordination between participants in the logistics process, as well as a high level of operating costs. An important task is the introduction of modern information and communication technologies that ensure the consistency of traffic schedules, operational data exchange and route optimization. This contributes to reducing transport downtime, reducing time and resource costs.Analysis of technical and technological forms of interaction allows not only to identify the main shortcomings, but also to determine promising areas for their improvement. In particular, the creation of multi-level transport hubs that provide a rapid change in the method of transporting goods, as well as the development of digital platforms for the integration of all participants in the logistics chain. The implementation of innovative solutions will contribute to the optimization of transshipment operations, improvement of working conditions of enterprises and increase of environmental efficiency.Thus, technical and technological integration of transport systems is a key condition for increasing the efficiency of their functioning. This allows reducing transportation costs, increasing the competitiveness of the national economy and contributing to environmental sustainability. Studying and improving the interaction of different modes of transport is an important task for the development of both national and international logistics systems.
Keywords: interaction of transport modes; intermodal transportation; innovative transport technologies; logistics processes; multimodal transportation; technical and technological forms; transport nodes; optimization of transportation routes